Foam-in-vein: rheological characterisation of liquid sclerosing foams using a pipe viscometer - Meghdadi, A; Jones, SA; Patel, VA; Lewis, AL; Millar, TM; Carugo, D (Elsevier, 2022)
Sclerotherapy is one of the most common and least-invasive treatment methods for varicose veins. While bench-top properties of sclerosing foams (e.g., bubble size distribution and foam half-life) have been studied previously, their flow behaviour and its relationship to therapeutic efficacy remain largely uncharacterised. To address this research gap, the present study reports on a novel approach for the rheological characterisation of sclerosing foams aimed at obtaining clinically-applicable data. A pipe viscometry apparatus was employed under conditions that mimic the end-point therapeutic application of foams. Polidocanol (1% v/v) foams of various liquid-to-gas volume ratios (1:3, 1:4 and 1:5) were formulated manually using the Tessari and DSS (double syringe system) methods across a clinically-relevant range of shear rates (≈ 7s−1 – 400s−1), in polytetrafluoroethylene pipes of different diameters (2.48 mm and 4.48 mm). Additionally, end-effect and wall-slip correction methods were utilised to model the nominal rheology of sclerosing foams. The rheological data were fitted into a power-law model to obtain fluid flow index (n) and fluid consistency index (K) of sclerosing foams, followed by an in-depth statistical analysis of the power-law indices. The observed rheological behaviour of sclerosing foams is shown to be dependent on vessel diameter and liquid-to-gas ratio, while the type of manual formulation technique used appears to be statistically insignificant towards foam rheology. Sclerosing foams behaved as shear-thinning fluids with observed flow indices ranging 0.238 < n < 0.445, while the observed consistency indices ranged 2.977 < K < 12.49. The nominal (end-effect corrected) rheology of foams was shown to follow similar trends concerning liquid-to-gas ratio and formulation technique, independent of the tube diameter. The power-law characterisation of sclerosing foam rheology provided evidence of a quasi-static drainage effect that affected foam viscosity during slower injections. Wall-slip correction failed to provide physically meaningful results and statistical analysis suggested that the type of manual formulation technique used has no impact on the outcome of sclerotherapy on larger varicosities. Overall, results suggest a direct correlation between foam dryness and viscosity. Based on the developed rheological model, this work also demonstrates that low injection flowrates could yield higher therapeutic efficacy in dilated varicose veins.